Estimating the contribution of influenza to hospitalisations in New Zealand from 1994 to 2008. Issue 33 (7th August 2015) - Khieu, Trang Q.T.; Pierse, Nevil; Telfar-Barnard, Lucy Frances; Huang, Q. Sue; Baker, Michael G.
Highlights A negative regression model was used to estimate the total impact of influenza on hospitalisations for all age and ethnic groups. Weekly counts of hospitalisations and isolates of influenza A, B and respiratory syncytial virus for the period 1994–2008 were input parameters for the model. Respiratory disease was the major contributor to influenza hospitalisations. Findings could provide a useful input into decisions about vaccination policy and would increase the estimated cost-effectiveness of interventions for the most vulnerable groups.